STRENGTHENING STUDENTS' SOCIAL-EMOTIONAL COMPETENCE THROUGH IPS LEARNING IN PRIMARY SCHOOL - Hermansyah, Hermansyah; Putri, Nurayzanil; Febriyanti, Prety; Elyani, Nur; Sarfian, Siti; Arfan, Arfan (Waniambey: Journal of Islamic Education, 2024)
Indonesia is a heterogeneous country with an extraordinary level of diversity in various aspects of life, including religion, culture, and language. This diversity affects people in interacting and communicating, of course, it will be difficult to adjust to the changes that occur in these different social environments. On the one hand, cultural diversity can add to the cultural repertoire of the nation, but on the other hand, it can have a negative impact on the fading of the nation's character. This can be seen from the many people who have individualism, intolerance, like to spread hoax news and use technology less wisely. The existence of this problem can trigger disharmony and disharmony in the social life of the community. Based on this phenomenon, it is necessary to take preventive action through education, one of which is by strengthening social studies learning in schools. The purpose of social studies learning itself helps students become good citizens and have social intelligence in maximising their role in the family and community environment. The method used in this study is a qualitative method using three data collection techniques, namely the first observation, second interview, third documentation. Then the researcher's data analysis technique uses the main data, namely data reduction, data analysis, and conclusions. Based on the results of the research that we observed how to strengthen the social spirit of children through social studies learning teachers provide understanding, support along with examples of behaviour that illustrates a positive social spirit towards students. The teacher becomes a roll model for students, the term teacher gives an example first how to behave socially towards peers, such as helping friends who are in trouble.